L’Aromathérapie au temps de la « peste » en France (XVIe-XVIIe siècles) - Koźluk, Magdalena (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
Historians of medicine often write of the psychosis and the omnipresent fear that, inthe Middle Ages, paralyzed the whole European population, due to the many mysteriesthat surrounded the plague, its origin, its inexplicable recurrence and its nature. Thesemysteries led to an abundance of treatises on the plague written in Latin as well as in thevernacular, which appeared in the XVIth and XVIIth centuries in France. Their authors,physicians, barber-surgeons and apothecaries, advanced theories and proposed efficientprophylactic treatments. Our research is principally concerned with the status of the proposedremedies, in particular on the importance of their aromas. We first consider the roleassigned to the quality of the air (climate, home), to its alterations and to the best meansof improving it (fumigation, incense). We then examine the aromatic composition of theremedies proposed, focusing on their forms and uses.